2003
DOI: 10.1002/mus.10476
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of HSPs to heat stress in slow and fast regions of rat gastrocnemius muscle

Abstract: In a recent study, we showed that the rat slow soleus and fast plantaris muscles exhibited different time courses for the response of specific heat shock proteins (HSPs) after 1 h of heat stress. We hypothesized that these differential responses were related, in part, to the varying fiber type composition of these muscles. To further test this hypothesis, we now have determined the responses of Hsp60, Hsp72, and Hsc73 during the 60 h following exposure to a single bout of heat stress in the deep (relatively hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Twenty-four hours following SWD, the treatment leg was re-measured to ensure that the second biopsy was taken from the exact location that SWD was performed. Based oV of the literature, we hypothesized that Hsp expression would be at its peak 24 h following heat treatment (Oishi et al 2003a;Selsby and Dodd 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four hours following SWD, the treatment leg was re-measured to ensure that the second biopsy was taken from the exact location that SWD was performed. Based oV of the literature, we hypothesized that Hsp expression would be at its peak 24 h following heat treatment (Oishi et al 2003a;Selsby and Dodd 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Animal models have shown that Hsp induction in skeletal muscle, occurs at temperatures over 40°C (Oishi et al 2003a;Selsby and Dodd 2005). Skeletal muscle heat shock can provide protection from oxidative stress (Selsby and Dodd 2005;Selsby et al 2007;Smolka et al 2000), reduce muscle wasting during immobilization (Naito et al 2000;Selsby and Dodd 2005), enhance regrowth (Selsby et al 2007), proliferation (Uehara et al 2004), and attenuate the severity of muscle damage (Maglara et al 2003;McArdle et al 2004;Miyabara et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers generally have considered and reported that the up-regulation of HSP proteins in cells is induced when the body temperature is elevated by 38C to 58C 38 or above 408C in animal models. 39 However, Nussbaum and Locke 40 showed that the increases in HSP from repeated ultrasound treatments were not due to increased temperature but likely due to the mechanical properties introduced to the cell. As discussed, shortwave diathermy has been shown to increase HSP expression in human skeletal muscle.…”
Section: Hsp70 and Hsp27p:tmentioning
confidence: 99%
“…Furthermore, overexpression of HSP27 also prevented muscle fiber atrophy of the soleus muscle induced by disuse in rats (5). HSPs are expressed in response to several types of stress such as heat (14,15) and exercise (12). Exercise increased HSP72 expression (2) and attenuated skeletal muscle fiber atrophy (3) in streptozotocin Nonaka K et al 294 (STZ)-induced diabetic rats.…”
mentioning
confidence: 99%